AN ANALYSIS OF ENGLISH-SPEAKING SKILLS MATERIALS FOR THE 11TH-GRADE STUDENTS OF MAN 1 MALUKU TENGAH - Dian Safitri; Syarifuddin Dollah; Chairil Anwar Korompot (INDOPEDIA (Jurnal Inovasi Pembelajaran dan Pendidikan), 2024)
The aims of this study are to determine the suitability of the English-speaking skills material to the needs of class 11 students at MAN 1 Maluku Tengah. This research uses a qualitative approach with a qualitative descriptive research design. The subjects of this research were 11th-grade English materials at MAN 1 Maluku Tengah, an English teacher, and seven 11th-grade students at MAN 1 Maluku Tengah. Data was collected using assessment checklists and interviews. The evaluation checklist was carried out offline at school and filled in by an 11th-grade English teacher and the researcher. Interviews with students are used to obtain information about students' needs regarding the English speaking-skill learning materials. Meanwhile, interviews with the teacher were conducted to obtain additional information regarding the English learning materials that she used. Student needs are divided into 3 aspects: necessities, lacks, and wants. From the research findings, the researcher concluded that the English-speaking skills are not yet appropriate to the student’s needs.